ChemInform Abstract: Palladium‐Catalyzed Carbonylations of Arylboronic Acids: Synthesis of Arylcarboxylic Acid Ethyl Esters. Issue 10 (February 2016) - Liang, Apeng; Han, Shuaijun; Wang, Liang; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract: Diethyl pyrocarbonate is successfully applied as substrate for the ethoxycarbonylation of (het)arylboronic acids.